ABANDONO FAMILIAR Y ESTADO EMOCIONAL EN ADULTOS MAYORES DE LA FUNDACIÓN ACCIÓN Y VIDA DEL CANTÓN CALUMA - CARRIEL MENDOZA AMBAR ELIZABETH (2024)
Well- Family abandonment refers to the lack of attention, support and care by family members towards one of its members, which may be intentional or unintentional. On the other hand, emotional state refers to your internal experiences of feelings and emotions, which affect your psychological and physical well-being. The present mixed research study deals with family abandonment and emotional state of older adults from the Fundación Acción y Vida del Cantón Caluma. The objective of this research is to determine family abandonment and emotional state of the elderly of the Acción y Vida Foundation of the Caluma canton. In this study, the mixed research methodology was used since through this methodology it relates elements of quantitative and qualitative research, which has made it possible to clearly and precisely verify the family abandonment and emotional state of older adults. It was considered to use a population of older adults from the Fundación Acción y Vida del Canton Caluma and a sample of 80 elderly people was taken from a total population of 100 where the study focus is family abandonment and emotional state.